New records of marine green algae (Ulvophyceae) from Tabasco, Mexico - Quiroz-González, Nataly; León-Álvarez, Daniel; Rivas-Acuña, Ma. Guadalupe (Instituto de Ecología, A.C., 2017)
Background and Aims: The knowledge of the phycoflora in the state of Tabasco is scarce, with 38 records of Rhodophyta, seven of Ochrophyta, and only five of Chlorophyta. Additionally, at national level it is the coastal state with the lowest number of publications about this topic. Therefore, this study was developed to contribute to the knowledge of its algal flora, particularly of Chlorophyta.Methods: Material of the herbaria of the Faculty of Sciences of the UNAM (FCME) and the Universidad Juárez Autónoma de Tabasco (UJAT) was revised. Two sampling periods were conducted during the rainy and dry seasons in seven locations on the coast of Tabasco. The collected material was preserved in formaldehyde at 4%. Observations of the thalli and sections were made with stereoscopic and light microscopes. Identification was carried out with specialized literature.Key results: Seventeen new records of species of green algae are presented for the coast of Tabasco, belonging to seven genera, five families and four orders. The orders with the highest species richness were Cladophorales and Ulvales, with eight and seven species, respectively. Families with the highest species number were Ulvaceae and Cladophoraceae with seven each. The most diverse genus was Ulva, with seven species.Conclusions: The number of seaweeds of the class Ulvophyceae registered in Tabasco rises from five to 22 records, representing 18% of Chlorophyta species recorded for the Gulf of Mexico. It is the first time that Chaetomorpha nodosa is reported for the coast of Mexico.